HUMAN TRAFFICKING IN THE PERSPECTIVE OF MAQASHID AL-SHARIA - Nurhayati, Nurhayati; Nasution, Muhammad Syukri Albani; Hasibuan, Reni Ria Armayani; Afendi, Hazrul (Islam Futura, 2022)
Islam is a religion that respects and upholds human values. Trafficking in persons is a form of modern slavery that is not following the nature of humanity given by God. This paper examines how trafficking in persons is in the perspective of maqashid al-sharia which aims to place humans in their human dignity.This paper uses a literature review by utilizing primary sources, whether in the form of books, research results, or journal works that have relevance to the focus of the study. Human trafficking is an act that is not relevant to the objectives of Islamic law, namely to create a life based on equality, independence, respect for fellow human beings, and worthiness in life. Islam forbids the behavior of trafficking in persons because Islam respects humans.In the conception of Islam, there are five main things called al-daruriyat al-khamsah (five main things that must be maintained). Namely protection of religion (hifzh al-din), soul (hifzh al-nafs), reason (hifzh al-'aql), offspring (hifzh al-nasl), property (hifzh al-mal). These five main things which are referred to as maqashid al-sharia are a specialty in Islamic teachings so that anything that contradicts them is considered as behavior that is not in accordance with the aims and objectives of the revelation of Islamic teachings.